Comparison of DNA extraction methods and real-time PCR assays for the molecular diagnostics of chronic Chagas disease - Silgado, Aroa (2020)
Fil: Ramírez, Juan C. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología DR: Mario Fatala Chaben; Argentina.